(untitled) (Research, Society and Development, 2022)
This study aims to describe the applications of telemedicine in the current scenario of the COVID-19 pandemic focusing in Brazil. This is a descriptive, qualitative study, carried out from a bibliographic survey about the positive and negative impacts of the use of telemedicine today. The literature was obtained from the SciELO, ResearchGate, PubMed and World Wide Science platforms. Telemedicine can become a fundamental tool to ensure universal access to health. It enables consultations and specialized care to be carried out remotely, reducing displacement costs and expanding access to healthcare by the population. With the security measures imposed with the SARS-CoV-2 pandemic, telehealth has become a practicable option to prevent the population from being exposed to the virus in the healthcare units. Despite that, there are challenges related to its use, such as the high cost, the resistance from health professionals and patients, regional inequalities and the lack of qualified professionals. Therefore, it is important to reflect on the applicability of telemedicine in the current Brazilian scenario. Although there are some difficulties regarding the adoption of telemedicine in our country, it is evident that it brings many benefits to the health systems. With the increase in investments in all Brazilian regions according to their needs, telemedicine will be able to solve recurrent challenges in the health system, by expanding the coverage of specialized services, improving the quality of care, reducing the time for diagnosis and therapy and cost reduction with displacement.